- NIELSEN COINCIDENCE POINT THEORY - AL-Ta'iy, Ban Jaffar (Al-Nahrain Journal of Science, 2018)
Let be maps of a compact connected Riemannian manifold, with or without boundary. For > 0 sufficiently small, we introduce an – Nielsen coincidence number that is a lower bound for the number of coincidence points of all self – maps that are - homotopic to f and g. We prove that there is always maps that is – homotopic to f and g such that and have exactly coincidence points.